Representasi Romantisme Dalam Lirik Lagu Karya For Revenge: (Kajian Semiotika Peirce) - Samuel Dhody Pratama; Syamsul Sodiq; Prima Vidya Asteria (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the representation of romanticism in the song lyrics of For Revenge using Charles Sanders Peirce’s semiotic approach. The research employed a qualitative descriptive method, with data sourced from six songs: Jentaka, Jakarta Hari Ini, Sadrah, Ada Selamanya, Pulang, and Serana. The data consisted of words, phrases, and sentences containing signs in the form of icons, indexes, and symbols that represent romanticism. Data were collected through documentation and note-taking techniques, while data analysis was conducted through sign identification, object interpretation, and meaning interpretation. The findings reveal that romanticism is represented through six major patterns: loss and emotional wounds, longing, maturity, sacrifice, enduring memories, and the search for life’s meaning. These representations are constructed through the interaction of icons, indexes, and symbols, producing complex, reflective, and philosophical meanings of romanticism. The study concludes that romanticism in For Revenge’s song lyrics is not only associated with love but also with broader existential human experiences.